Kinetic Theory-Based Methods in Fluid Dynamics - Chen, Zhen; Zhang, Liangqi; Yang, Liming (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Kinetic theory stems from statistical mechanics established at the mesoscopic scale. The numerical methods established on kinetic theory perform unique and important roles in almost all studies of fluid dynamics. This reprint reports the recent advances in this vibrant community. The development of kinetic theory-related numerical schemes and their applications to fluid dynamics problems are the main focus.